Very high‐resolution digital elevation models: are multi‐scale derived variables ecologically relevant?. Issue 12 (31st July 2015) - Leempoel, Kevin; Parisod, Christian; Geiser, Céline; Daprà, Lucas; Vittoz, Pascal; Joost, Stéphane
Summary: Digital elevation models (DEMs) are often used in landscape ecology to retrieve elevation or first derivative terrain attributes such as slope or aspect in the context of species distribution modelling. However, DEM‐derived variables are scale‐dependent and, given the increasing availability of very high‐resolution (VHR) DEMs, their ecological relevance must be assessed for different spatial resolutions. In a study area located in the Swiss Western Alps, we computed VHR DEMs‐derived variables related to morphometry, hydrology and solar radiation. Based on an original spatial resolution of 0·5 m, we generated DEM‐derived variables at 1, 2 and 4 m spatial resolutions, applying a Gaussian Pyramid. Their associations with local climatic factors, measured by sensors (direct and ambient air temperature, air humidity and soil moisture) as well as ecological indicators derived from species composition, were assessed with multivariate generalized linear models (GLM) and mixed models (GLMM). Specific VHR DEM‐derived variables showed significant associations with climatic factors. In addition to slope, aspect and curvature, the underused wetness and ruggedness indices modelled measured ambient humidity and soil moisture, respectively. Remarkably, spatial resolution of VHR DEM‐derived variables had a significant influence on models' strength, with coefficients of determination decreasing with coarser resolutions or showing a local optimum with a 2 m resolution, depending on the variable considered. These results support the relevance of using multi‐scale DEM variables to provide surrogates for important climatic variables such as humidity, moisture and temperature, offering suitable alternatives to direct measurements for evolutionary ecology studies at a local scale.